2020
DOI: 10.1088/1757-899x/862/5/052065
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of types of signs for a task of the regression analysis

Abstract: Today there are a large number of methods and analysis algorithms of data for solution of problems of image identification, automatic classification, component, correlation and regression analysis which in case of availability of data of the different type nature become inapplicable because they are intended only for processing of quantitative information. The approach to solution of this problem named conversion of types of signs for a problem of regression analysis is described in the offered article. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…At that, a particular attention is paid to the modeling of various subsystems in the automation of the agricultural sector. These problems are well studied in various branches of science and technology: in modeling in geomechanics [11][12][13], in solving problems of pattern recognition [14][15][16][17][18] and classification [19,20], medicine [21], in tracking objects based on a Kalman filter [22], modeling of personal identification processes [23], creating a model of an access control system [24], creating models to improve image contrast [25], when modeling predictive indicators [26] and in sports research [27], as well as in hydromechanics [29,29]. In our case, for modeling and automatic control of the agricultural sector, the PHP programming language and the MySQL database, as well as various methods of data mining [30,31], were used.…”
Section: Resultsmentioning
confidence: 99%
“…At that, a particular attention is paid to the modeling of various subsystems in the automation of the agricultural sector. These problems are well studied in various branches of science and technology: in modeling in geomechanics [11][12][13], in solving problems of pattern recognition [14][15][16][17][18] and classification [19,20], medicine [21], in tracking objects based on a Kalman filter [22], modeling of personal identification processes [23], creating a model of an access control system [24], creating models to improve image contrast [25], when modeling predictive indicators [26] and in sports research [27], as well as in hydromechanics [29,29]. In our case, for modeling and automatic control of the agricultural sector, the PHP programming language and the MySQL database, as well as various methods of data mining [30,31], were used.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, all the signs (columns) of the TED must be quantitative (all mathematical operations are performed). The qualitative signs, there were applied methods of transforming the types of signs [8], allowing by digitization to translate these signs into quantitative. In the mathematical modeling of the issue under study were used the methods proposed in [9].…”
Section: Resultsmentioning
confidence: 99%
“…The work uses the following methods: intellectual data analysis [1][2][3][4][5][6][7], feature type conversion [8,9], interval analysis methods [10,11], a technique for searching for hidden patterns in the initial information [12,13], questionnaires of athletes and coaches, sports tests, statistical methods.…”
Section: Methodsmentioning
confidence: 99%
“…The course "Information technologies and mathematical modeling of processes" describes the modeling methods proposed in [11][12][13][14], modeling methods used in geodynamics [15][16][17], the original methods of pattern recognition [18][19][20][21][22][23], methods of reducing the dimension of the initial feature space for the problem of pattern recognition in relation to solving medical and other problems [24][25][26][27][28][29][30]. Also included in the course are: results of studies of the spectra of electron paramagnetic resonance and infrared rays in order to consider the possibility of changing the interfacial layer of the nanocomposite [31]; the results of electron microscopic studies of morphology and X-ray diffraction analysis of the phase composition of the nanocomposite, where it is shown that the dispersed phase mainly consists of nanoparticles of metallic copper with a size of 33.94 nm [32]; the results of studies of the frequency dependence of the conductivity of compositions based on glass and cadmium oxide [33].…”
Section: Discussionmentioning
confidence: 99%